Emergency Medicine Morbidity and Mortality Conference and Culture of Safety: The Resident Perspective. Issue 3 (4th May 2017) - Wittels, Kathleen; Aaronson, Emily; Dwyer, Richard; Nadel, Eric; Gallahue, Fiona; Fee, Christopher; Tubbs, Robert; Schuur, Jeremiah; ,
Abstract: Objective: Morbidity and mortality conference (M&M) is common in emergency medicine (EM) and an Accreditation Council for Graduate Medical Education (ACGME) requirement. We aimed to characterize the prevalence of elements of EM M&M conferences that foster a strong culture of safety. Methods: Emergency medicine residents at 33 programs across the United States were surveyed using questions adapted from a previously tested survey of EM program directors and the Agency for Healthcare Research and Quality (AHRQ) Culture of Safety Survey. Results: The survey response rate was 80.3% (1, 002/1, 248). A total of 60.3% (601/997) of residents had not submitted a case of theirs to M&M in the past year. A total of 7.6% (73/954) reported that issues raised at M&M always led to change while 88.3% (842/954) reported that they sometimes did and 4.1% (39/954) reported that they never did. A total of 56.2% (536/954) responded that changes made due to M&M were reported back to the residents. Of residents who had cases presented at M&M, 24.2% (130/538) responded that there was regular debriefing, 65.2% (351/538) responded that there was not, and 10.6% (57/578) were unsure. A total of 10.2% (101/988) of respondents agreed that M&M was punitive, 17.4% were neutral (172/988), and 72.4% (715/988) disagreed. A total of 18.0% (178/987) of residents agreed that they felt pressure to order unnecessary tests because of M&M, 22.3% (220/987) were neutral, and 59.6% (589/987) disagreed. A total of 87.4% (862/986) felt that M&M was a valuable educational didactic session, and 78.3% (766/978) believed that M&M contributes to a culture of safety in their institution. Conclusions: While most residents believe that M&M is a valuable didactic session and contributes to institutional culture of safety, there are opportunities to improve by communicating changes made in response to M&M, debriefing residents who have had cases presented, and taking steps to make M&M not feel punitive to some residents.